Games in vocabulary teaching for elementary students - Nagy Andrea; Sinka Hilda (2002)
Teaching and learning vocabulary is one of the most important fields of teaching a foreign language. It is a long process; it can be done in an interesting way, which can encourage students to learn a language pleasantly. In this thesis I will examine the principles of teaching vocabulary for young learners. Then I will give the general characteristic of these children. I will demonstrate some traditional techniques and compare them with the use of language games for vocabulary presentation and revision. I will prove that games are more successful in vocabulary teaching than other techniques.
Keywords: Pedagógusképzés